2020
DOI: 10.1002/jemt.23536
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cadmium toxicity and its possible effects on goldfish (Carassius auratus), employing microscopy and biochemical techniques

Abstract: The present study aimed to evaluate and compare the toxicity level of dietary and waterborne Cadmium (Cd) source on the Goldfish Carassius auratus (C. auratus) using various biochemical and microscopic shreds of evidence. C. auratus were divided into two groups based on Cadmium supplementation methods subjected to the same concentrations in the diet and water; moreover, control (Ctrl) group was set up for comparison. Dietary supplemented group (DSG) group and (Aqueous supplemented groups) ASG were supplied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…With the increase in Cd concentration, the degree of irreversible damage to the structure of fish liver cells also increases significantly, which mainly includes endoplasmic reticulum expansion, nuclear deformation, nuclear membrane mitochondrial swelling, distortion, granular cytoplasm, and cell edema and cavitation. When the liver tissue structure is destroyed, the detoxification ability of the liver is significantly reduced, which has an irreversible impact on growth, reproduction, and survival [ 17 , 95 , 96 ].…”
Section: Toxic Effects Of Cadmium Accumulation On Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase in Cd concentration, the degree of irreversible damage to the structure of fish liver cells also increases significantly, which mainly includes endoplasmic reticulum expansion, nuclear deformation, nuclear membrane mitochondrial swelling, distortion, granular cytoplasm, and cell edema and cavitation. When the liver tissue structure is destroyed, the detoxification ability of the liver is significantly reduced, which has an irreversible impact on growth, reproduction, and survival [ 17 , 95 , 96 ].…”
Section: Toxic Effects Of Cadmium Accumulation On Fishmentioning
confidence: 99%
“…If fish are exposed to Cd pollution for a long time, their different tissues will absorb and accumulate Cd, thus affecting the structure and function of the gills, liver, and gonad. Furthermore, Cd affects their physiological metabolism and reproductive and immune systems and eventually leads to metabolic disorders, physical disorders, or even death [ 16 , 17 , 18 ]. Recently, studies have shown that Cd can induce various epigenetic changes, thus, changes occur in the chemical modification of DNA, histones, and chromatin, but not the sequence of DNA nucleotides, including DNA methyltransferase, histone acetyltransferase, histone deacetylase, histone methyltransferase, and microRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Adding Cd 2+ to the dietary and water not only leds to distinct damages to the outer skin, scales, and gills of gold sh, but also causes inner damages in different organs such as gills lamella shrunk and broken, the necrotic muscles myoepithelium along with disrupted muscles bundle, and abnormal dilations in the liver cells (Noor et al 2020). Cd 2+ also caused the decrease of respiratory function in the freshwater crab Barytelphusa gureini, gill hyperplasia and degenerative changes in visceral organs, elevation in MDA and attenuation in GSH activity in Oreochromis niloticus (Abu-Elala et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The exposure of freshwater biota to endocrine-disrupting metals like Cd can have significant implications for the population dynamics of affected fish species. Reduced fertility, skewed sex ratios, and altered reproductive behavior can lead to decreased population size and genetic diversity, which can have long-term effects on the survival and viability of a species [17]. Due to the crucial involvement of the endocrine system in regulating homeostasis and other physiological processes, the study of the effects of such a disruption may be significant.…”
Section: Introductionmentioning
confidence: 99%